IMPLEMENTASI APLIKASI LARISA (LAYANAN MANDIRI MASYARAKAT DESA) DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DESA CENGKUANG KECAMATAN PALIMANAN KABUPATEN CIREBON - Aji Mujahid Fadhilah; Rochmat Hidayat; Hesti Nauli Fitri Agasya; Agus Rianto (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2026)
Digital transformation in village governance has become an important strategy for improving the quality of public services, particularly population administration services. The Government of Cengkuang Village, Palimanan District, Cirebon Regency developed the LARISA (Village Community Self-Service) application as a digital public service innovation to facilitate faster, easier, and more efficient administrative services for the community. This study aims to analyze the implementation of the LARISA application in population administration services in Cengkuang Village. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. Policy implementation was examined using George C. Edward III's framework, consisting of communication, resources, disposition, and bureaucratic structure, while community satisfaction was analyzed using the Expectancy Disconfirmation Theory. The findings indicate that the implementation of the LARISA application has been successfully carried out and has contributed positively to improving the quality of population administration services. The successful implementation is supported by effective communication, adequate resources, committed village officials, and a well-defined bureaucratic structure. The application has enabled public services to become faster, more effective, more efficient, and more transparent than the previous manual system. However, several challenges remain, including limited digital literacy among some community members and unstable internet connectivity. The study concludes that the LARISA application has become an effective public service innovation that improves both the quality of population administration services and community satisfaction. Nevertheless, strengthening human resource capacity, expanding public outreach, and improving information technology infrastructure are necessary to ensure the sustainability and optimization of digital public services.